GROWING UP DURING NORMALIZATION IN TRAGICOMIC AND NOSTALGIC NARRATION - Spacek, Martin (Bohemica Olomucensia, 2021)
This study examines the significant amount of popular Czech prose published after 1989 that addressed growing up during the late communist era of 'normalization' (1970s and 80s). The prose of P. Sabach, M. Viewegh, I. Douskova, H. Pawlowska, J. Formanek and B. Vanek Uvalsky have much in common: adolescent or distant narrators and acts of small and funny resistance against the regime, but also a lack of interest in politics, memories of pop-culture, first love and partying. Much of this is related to the well-known phenomenon of "ostalgia" or "post-socialist nostalgia", meaning nostalgic reminiscences of the communist era. The study also connects all texts with the widespread "silent majority" discourse after 1989, in which most people denied their participation in communist totalitarianism, seeing themselves as oppressed by the regime.
Keywords: normalization; post-socialist nostalgia; ostalgia; silent majority; tragicomic novel